Phytochemical screening,antioxidant capacity and toxicological study of Malaysian Peperomia pellucida (L.) Kunth - Amirah Shaari (Tanjong Malim, 2019)
Phytochemical screening,antioxidant capacity and toxicological study of Malaysian Peperomia pellucida (L.) Kunth by Amirah Shaari